(untitled) (Oratio Directa, 2025)
This qualitative phenomenological study examines the individual spiritual meanings attributed to pilgrimage at the tomb of Sultan Maulana Hasanuddin in Banten. Data were generated through observation and in-depth interviews with five pilgrims identified by the pseudonyms Ki, Pak Sho, Pak Iw, Pak Fa, and Bu Ay. The analysis indicates that pilgrimage is understood as a moment for renewing faith, strengthening worship, seeking spiritual balance, remembering mortality, and building emotional and spiritual ties with fellow pilgrims. Prayer, remembrance, Qur'anic recitation, and reflection are described as practices that connect pilgrims with God and provide calm when facing everyday difficulties. Pilgrimage is also interpreted as silaturahmi that links personal experience, religious tradition, and community. The source, however, does not report participant recruitment, demographic profiles, interview duration, analytic stages, reflexivity, member checking, or data saturation. The findings therefore represent the accounts of five participants at one site and should not be generalized to all pilgrims. The study concludes that individual spiritual meaning combines an existential dimension of purpose and social connection with a religious dimension centered on worship and the relationship with God.